Prediction of grain boundary chemistry in multicomponent Mo alloys with coupled precipitation and segregation kinetics simulations. (1st February 2022) - Scheiber, Daniel; Povoden-Karadeniz, Erwin; Kozeschnik, Ernst; Romaner, Lorenz
Abstract: Simulations are carried out to predict the amount of dissolved solute contents in multi-component Mo-based alloys containing Hf, Ti, C and O during and after a model thermo-mechanical treatment. The results are used to model the amounts of C, O and Hf in grain boundaries after heat treatment with concurrent precipitation in the corresponding alloys and to correlate this to measured atom probe tomography data of grain boundary enrichment. Our unique combinatory approach that considers precipitation and segregation at the same time allows for successful prediction of grain boundary enrichment. Graphical Abstract: Image, graphical abstract